Plant Phylogeny and Growth Form as Drivers of the Altitudinal Variation in Woody Leaf Vein Traits - Wang, Ruili; Chen, Haoxuan; Liu, Xinrui; Wang, Zhibo; Wen, Jingwen; Zhang, Shuoxin (Frontiers in Plant Science, 2020)
Variation in leaf veins along environmental gradients reflects an important ecological strategy of plants to adapt to its habitat because their crucial roles in maintaining leaf water status and photosynthetic capacity. However, most studies concentrate on variation of vein traits across horizontal spatial scale, and we know little about how they shift along the vertical scale, e.g., elevation gradient along a mountain forest, and whether such patterns are shaped by the plant and environmental factors. Here, we aimed to investigate the leaf vein traits (i.e., vein density, VD; vein thickness, VT; and vein volume per unit leaf area, VV) of 93 woody species distributed along an elevation gradient (1374–3375 m a.s.l.) in a temperate Mountain in China. Our results showed that altitude-related trends differed between growth forms. Tree plants from higher altitudes possessed lower VD but higher VT and VV than those from lower altitude, however, the opposite tend was observed in VD of shrubs, and no significant altitudinal changes in their VT or VV. Plant phylogenetic information rather than climate explained most of variation in three leaf vein traits (17.1–86.6% vs. <0.011–6.3% explained variance), supporting the phylogenetic conservatism hypothesis for leaf vein traits. Moreover, the phylogenetic effect on vein traits differed between trees and shrubs, with the vein traits of trees being relatively more conserved. Together, our study provide new picture of leaf vein variation along the altitude, and showed the role of plant phylogeny and functional type in driving vein trait variation.